An extended UTAUT model of factors affecting Malaysian undergradutes’ ICT skills / Ayad A Yass - Ayad, A Yass (2018)
Information and Communication Technology has become one of the fundamental skill that higher education institution students need to acquire and grasp in preparation for future employment. Although ICT has been the most dominant ubiquitously in people life nowadays; the student’s ICT skills penetration has been relatively low. The purpose of this correlational quantitative study is to explore the factors affecting and effecting student’s ICT skills. The constructs used to develop the web-based survey for this study were derived from the Unified Theory of Acceptance and Use of Technology extended model. Data were collected by sending e-mails to a random sample of 504 students for 18 public universities in Malaysia. The structured equation modeling technique was used to assess correlations between the extended Unified theory of acceptance and use of technology constructs as the independent variables (also known as the exogenous factors) with intention to use ICT as the dependent variable. The findings of this study indicated that attitude, anxiety, effort expectancy and facilitating condition are the significant factors affecting High educational institute students’ ICT skills in Malaysia. A framework is develop based on the result of the research hypothesis. The purpose of developing this framework is to identify significant factors affecting student’s ICT skills and also as a guide future empirical research into the differences affect and effect factors in HEI students’ ICT skills. The findings of this research suggests useful insight to the HEI to provide useful recommendation to facilitate procedures to improve the factors that affect and effect ICT skill of students in HEI.